Entrepreneurial development initiatives on business sustainability in small and medium enterprises (SMEs) in South West Nigeria - Opeyemi Jumoke Zubair; Ayotunde Isaac Bankefa; Bayo Abraham Ogunyanju (CV. Literasi Indonesia, 2026)
The study addresses the ongoing sustainability issues faced by agricultural SMEs in Southwest Nigeria, despite many entrepreneurial development initiatives focused on innovation, technology adoption, and governmental assistance. This study explicitly analyses the impact of innovation and technology adoption on the sustainability of agricultural SMEs and assesses the role of government policies and support measures in bolstering their resilience against the region's changing economic landscape. The research employs a quantitative survey design with a study population of 385. Data were collected from agricultural SME operators using structured questionnaires, and the gathered data were analysed using descriptive and inferential statistics. The findings revealed that, despite the perceived insufficiency of government support being relatively low, innovation and technology adoption, combined with government support and policies, exert a statistically significant collective influence on the sustainability of agricultural SMEs, accounting for a considerable portion of the variance in sustainability outcomes. This indicates that, while agricultural entrepreneurs are aggressively using technology and new techniques to enhance performance, the advantages are limited by inconsistent, inadequate, or poorly executed support mechanisms. The study recommends that improving the long-term sustainability of agricultural SMEs in Southwest Nigeria necessitates not only the dissemination of innovation and digital tools but also a purposeful redesign of government policies and programs to ensure they are more stable, accessible, and responsive to the distinct needs of agricultural enterprises.